Sex Differences in Receipt of Bystander Cardiopulmonary Resuscitation Considering Neighborhood Racial and Ethnic Composition - Audrey L. Blewer; Monique A. Starks; Carolina Malta‐Hansen; Comilla Sasson; Marcus Eng Hock Ong; Rabab Al‐Araji; Bryan F. McNally; Anthony J. Viera (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Bystander cardiopulmonary resuscitation (B‐CPR) and defibrillation for out‐of‐hospital cardiac arrest (OHCA) vary by sex, with women being less likely to receive these interventions in public. It is unknown whether sex differences persist when considering neighborhood racial and ethnic composition. We examined the odds of receiving B‐CPR stratified by location and neighborhood. We hypothesized that women in predominantly Black neighborhoods will have a lower odds of receiving B‐CPR. Methods and Results We conducted a retrospective study using the Cardiac Arrest Registry to Enhance Survival (CARES). Neighborhoods were classified by census tract. We modeled the odds of receipt of B‐CPR (primary outcome), automatic external defibrillation application, and survival to hospital discharge (secondary outcomes) by sex. CARES collected 457 621 arrests (2013–2019); after appropriate exclusion, 309 662 were included. Women who had public OHCA had a 14% lower odds of receiving B‐CPR (odds ratio [OR], 0.86 [95% CI, 0.82–0.89]), but effect modification was not seen by neighborhood (P=not significant). In predominantly Black neighborhoods, women who had public OHCA had a 13% lower odds of receiving B‐CPR (adjusted OR, 0.87 [95% CI, 0.76–0.98]) and 12% lower odds of receiving automatic external defibrillation application (adjusted OR, 0.88 [95% CI, 0.78–0.99]). In predominantly Hispanic neighborhoods, women who had public OHCA were less likely to receive B‐CPR (adjusted OR, 0.83 [95% CI, 0.73–0.96]) and less likely to receive automatic external defibrillation application (adjusted OR, 0.74 [95% CI, 0.64–0.87]). Conclusions Women with public OHCA have a decreased likelihood of receiving B‐CPR and automatic external defibrillation application. Findings did not differ significantly according to neighborhood composition. Despite this, our work has implications for considering strategies to reduce disparities around bystander response.